Depressive symptoms and oral mucositis in children with oncological diseases: a cross-sectional study - Felipe Barreto LEMOS; Andressa Chang Fernandes Rodrigues da SILVA; Fernanda Pereira LIMA; Fernanda Conceição MACHADO; Luanderson Lopes PEREIRA; Arnaldo França CALDAS; Bruna Bustani dos SANTOS; Andréia Cristina Leal FIGUEIREDO (Sociedade Brasileira de Pesquisa Odontológica, 2024)
Abstract The aim of this study was to investigate the correlation between depressive symptoms and the occurrence of oral mucositis in children with oncological diseases treated at a reference hospital. This was a cross-sectional study conducted with individuals aged 4 to 18 years, diagnosed with primary neoplasms. Data was collected by using a questionnaire that assessed the degree of oral mucositis according to the World Health Organization index, the risk of oral mucositis according to the Child's International Mucositis Evaluation Scale, and depressive symptoms using the Children's Depression Inventory. The data were analyzed and subjected to Spearman's correlation, chi-square test, and Fisher's exact test, considering p<0.05. A statistically significant correlation was observed between depressive symptoms and the degree of oral mucositis (p = 0.044), and also between the "pain" variable within the risk of oral mucositis and depressive symptoms (p = 0.021). Based on the findings, it can be inferred that oral mucositis may be associated with the development of depressive symptoms and may be influenced by the individual's hospitalization, thereby affecting the quality of life of pediatric patients.